Comparison of different sample pre‐treatments for multi‐residue analysis of organochlorine and pyrethroid pesticides in chrysanthemum by gas chromatography with electron capture detection. Issue 7 (8th March 2013) - Xue, Jiaying; Xu, Yanjun; Liu, Fengmao; Xue, Jian; Li, Huichen; Peng, Wei
<x xml:space="preserve">Abstract</x> The widespread use of insecticides in Chinese herbal medicines has created a compelling need for the development of a multiresidue analytical method to help assure herbs safety. The operating variables affecting the performance of the multiresidue analysis of 34 organochlorine and 12 pyrethroid pesticides in chrysanthemum, a widely used kind of Chinese herbal medicines, were evaluated. Three different extraction solvents including n‐hexane and its mixtures with acetone and petroleum ether were compared, and n‐hexane was found to be an appropriate option. A combination of gel permeation chromatography and SPE was selected as the optimum cleanup, in comparison with dispersive SPE, or the two former methods alone. The determination of the 46 pesticide residues in the spiked chrysanthemum samples was performed by GC with electron capture detection. The average recoveries ranged from 71.3 to 102.6% with RSDs of 1.4–15.7% for all of the pesticides. The LOQs were in the range of 0.0015–0.2 mg/kg, while the LODs were between 0.0005 and 0.1 mg/kg. The satisfactory accuracy, and precision, in combination with a good separation and few interferences, have demonstrated the strong potential of this technique for its application in chrysanthemum analysis.